EBV in situ hybridization study for non-Hodgkin's lymphomas. - Ko, Y. H. (Korean Academy of Medical Sciences, 1994)
Epstein-Barr virus(EBV) has been implicated in the pathogenesis of B-lymphoproliferative disorders, T-cell lymphomas and Hodgkin's disease. In this report, we performed an in situ hybridization study on EBV genome in 10 cases of nasal non-Hodgkin's lymphoma(NHL), 20 cases of Waldeyer's ring(WR) NHL, and 20 cases of nodal NHLs to document EBV association with lymphomas in Koreans. For immunophenotyping, monoclonal antibodies for CD 20, MB 2, CD 45Ro & CD 43 were used. For in situ hybridization study, EBV DNA probe for Bam HI 'V' fragment and EBV RNA probe for EBER and BHLF were used. Twenty two cases(44%) of malignant lymphomas were positive for EBV genome. Generally, T-cell lymphomas showed a higher positive rate(61%) than B-cell lymphomas(24%). Among T-cell lymphomas, nasal lymphomas showed a higher positive rate(80%) than WR(50%) or nodal lymphomas(50%). Of 22 EBV genome positive cases, 10 cases were positive for EBER, 10 cases for BHLF, and 2 cases for both EBER and BHLF. The histologic types by Working Formulation(WF) were not correlated with EBV genome positive rate, whereas lymphomas showing the histologic spectrum of polymorphic reticulosis(PR) showed a higher positive rate(65%) than lymphomas without PR-like features(40%). These results indicate that nasal T-cell lymphomas with the histologic spectrum of PR are strongly associated with EBV and that the anatomic site may be an important factor in this association.